Evaluation of Post Obturation Pain Associated with Tricalcium Silicate and Resin-Bond Root Canal Sealer in Single Visit Root Canal Treatment- Quasi-Experimental Study: Post Obturation Pain with Tricalcium Silicate and Resin-Bond Root Canal Sealer - Ejaz, Tahira; Al Absi, Mowaffaq Abdullmomen; Memon, Kareema; Ghani Shaikh, Abdul; Bibi, Batool; Salman, Saima; Shams, Salman (Pakistan Journal of Health Sciences, 2024)
Despite advancements in root canal sealers, post-obturation pain remains a concern for both patients and clinicians. Objectives: To compare the post-obturation pain associated with tricalcium silicate and resin-bond root canal sealer. Methods: This quasi-experimental study was conducted at Liaquat University of Medical and Health Sciences, Jamshoro, Hyderabad, using non-probability consecutive sampling on 254 patients. Participants, aged 18 to 45, needed root canal therapy on a permanent single-rooted tooth with a single canal with irreversible pulpitis without apical periodontitis. Group A received AH Plus resin-based sealer, while Group B was treated with BioRoot RCS calcium silicate-based sealer. Root canal procedures followed endodontic guidelines, including pulp testing, anesthesia, canal shaping with nickel-titanium rotary files, obturation with gutta-percha and sealers, and composite resin restoration. The visual analogue scale assessed Pain and treatment efficacy at 24 hours and 7 days post-obturation. Results: Group A had 46 male (36.2%) and 81 female (63.8%) with a mean age of 30.2 years (11.2), while Group B had 59 male (46.5%) and 68 female (53.5%) with a mean age of 34.5 years (12.4). At 24 hours, postoperative pain was significantly lower in Group B (3.13 ± 1.23) than in group A (3.59 ± 1.38, p=0.008), while pain differences were not significant preoperatively (p=0.78) or after seven days (p=0.08). Conclusions: It was concluded that in single-visit root canal treatment, both BioRoot root canal sealers (Septodont) tricalcium silicate-based sealer and AH Plus (Dentsply) resin-based sealer demonstrated similar efficacy in post-obturation pain.